Rate control for VBR video over ATM: simplification and implementation - Yan Yang; Hemami, S.S. (IEEE transactions on circuits and systems for video technology, 2001)
Rate control is essential to ensure high-quality video transmission over asynchronous transfer mode (ATM) networks; both source and channel rates must not violate buffer or network traffic constraints in order to guarantee decoded video quality. To date, source and channel rate selection has been performed jointly because the rates are related through buffer and network constraints and therefore appear to be interdependent. It is shown that selection of these rates can be separated and the rate control problem is therefore simplified, allowing sequential source and channel rate selection without the need for iteration. A rate control algorithm is proposed which implements noniterative, separate sequential selection of source and channel rates in order to minimize the distortion variation between frames, subject to all buffer and network constraints. In particular, the leaky bucket is used as the traffic policing mechanism. Achieving a target rate for individual frames is facilitated by using a rate-distortion optimized video coder which allows coding to an exactly specified rate or distortion. Channel rate selection is performed following source rate selection with the goal of providing smooth traffic to the network, thereby allowing a high statistical multiplexing gain. Experiments demonstrate that the proposed noniterative rate control algorithm, when implemented using the optimized coder, achieves consistent video quality while providing smooth traffic to the network.